The CAD and Simulation Technololgy of the NC Shaping Program of Noncircular Gear - 徐晓俊; 李华忠; 唐德威; 高业田 (Jixie chuandong)
In this paper,the CAD and graphic simulation technology of the NC shaping program of the noncircular gear was discussed according to the working principle of gear shaping machine and the theory of conjugated surfaces,and the data preprocessing method of the noncircular gear pitch curve was proposed.In order to see the machining character of the designed pith curve,the graphic simulation technology was used to display the machining process, and snap the enlarged tooth profice.